Implementasi Teknologi Digital Dalam Pemasaran Usaha Sayur Hidroponik Surabaya - Aini Mufidah, Ismi; Ayu Aulia, Melly Eka; Dewi Safitri, Kartika; Ikhwan Abdillah, Mohammad; Rahmawati, Lilik (EKONOMI DAN BISNIS DIGITAL, 2024)
This article examines digital implementation in marketing hydroponic vegetable businesses with a focus on hydroponic vegetable garden businesses in Surabaya. The main aim of this article is to understand how digital technology has become an important instrument in marketing hydroponic vegetable businesses. This article uses a qualitative approach with interview, observation and literature study methods to collect data from the Surabaya Vegetable Garden. The results of the article show that the digital technology used for marketing hydroponic vegetables has had a significant positive impact on the business at the Surabaya Vegetable Garden. Implementation of digital technology in marketing, which includes sales and promotions carried out on social media for hydroponic vegetables in the Surabaya Vegetable Garden by utilizing current technology. This article contributes to the understanding of digital technology used in the marketing system by Kebun Sayur Surabaya and the policy implications resulting from this article are the need to increase the effectiveness and efficiency of digital marketing.